Suicidal Ideation Among High School Students From the West of Tehran, Iran: A Cros-sectional Study - Arman Naeemi; Marjan Mardani-Hamooleh; Nasanin Esmaeeli; Shima Haghani (Iran University of Medical Sciences, 2023)
Background & Aims Suicide and suicidal thoughts among adolescents have become a worrying psychosocial problem. This study aims to evaluate suicidal ideation among adolescents from the west of Tehran, Iran. Materials & Methods In this descriptive cross-sectional study, 256 boys and girls were selected from second-grade high schools in the west of Tehran by a convenience sampling method in 2022. The data collection tools were a sociodemographic form and the Beck scale for suicidal ideation (BSSI), which were completed using a self-report method. The collected data were analyzed in SPSS software, version 16 using descriptive and inferential statistics (independent t-test, analysis of variance). Results The mean age of the participants was 17.33±0.67 years. The mean score of BSSI was 3.19±5.66 out of 5. Among the sociodemographic factors, suicidal ideation had a statistically significant relationship only with the grade point average (P=0.004). Conclusion It is recommended to design and implement programs to educate and provide psychiatric services to high school students in Iran to reduce their suicidal ideation.